RESISTÊNCIA INSULÍNICA, ASMA E DEPRESSÃO: existe um quadro sindêmico em jovens? - FALCÃO, Aline Sousa (2024)
Introduction: The burden of Chronic Noncommunicable Diseases (NCDs) has increased in adolescents due to exposure to risk behaviors, such as smoking, physical inactivity, unhealthy diet and harmful use of alcohol, which can have repercussions on insulin resistance, asthma and depression. The syndemic approach makes it possible to examine how certain diseases group together synergistically and affect the population in a context of social vulnerability. The objective of the study was to develop and analyze a syndemic model covering the role of social determinants, metabolic risk, asthma and depression in young people. Methods: This is a population-based study carried out with 2515 adolescents aged 18 and 19 belonging to the Brazilian Consortium of Birth Cohorts RPS (Ribeirão Preto, Pelotas and São Luís), from São Luís – MA. A theoretical model was proposed to analyze the syndemic association between insulin resistance, asthma and depression in young people, through Structural Equation Modeling (SEM). The latent variables were Socioeconomic Status (SES), considered an ancestral determinant exerting an effect on the other variables in the model, and Asthmatic Phenotype, deduced by the shared variance of the indicators obtained from the following questions in the questionnaire: Have you ever had wheezing in your life? chest? Have you ever had asthma in your life? Have you ever been told by your doctor that you had asthma or bronchitis? And since last year, how many attacks of wheezing have you had? And the outcomes of interest were depression and asthma. Depression was based on the diagnosis of the presence of a major depressive episode and recurrent major depressive episode from the Mini International Neuropsychiatric Interview (M.I.N.I.). The metabolic variables consisted of the Triglycerides and HDL-cholesterol ratio (TG/HDL-c) and obesity. Results: The lower socioeconomic status explained the higher levels of TG/HDL-c (standardized coefficient - CP = 0.55; p= 0.029) and depression (CP=0.069; p=0.002). Higher tertiles of the TG/HDL-c ratio were directly associated with the Asthmatic Phenotype (CP= 0.062; p=0.049), and indirectly with depression (CP= 0.013; p=0.049). The asthmatic phenotype was associated with depression (CP= 0.094; p< 0.001). Female gender was associated with obesity (SC = 0.132; p< 0.001) and depression (SC = 0.161; p < 0.001). Conclusion: Taken together, our findings can support the implementation of public policies aimed at adolescents in the integrated prevention and control of risk behaviors in young people, and that can help reduce the prevalence and impact on insulin resistance, asthma, and depression simultaneously.